Nonalcoholic Fatty Liver Diseases among Recently Diagnosed Patients with Diabetes Mellitus and Risk Factors - Butt, Amna S (Euroasian J Hepatogastroenterol, 2019)
AIM: Prevalence of obesity and type 2 diabetes mellitus (T2DM), both of which represent are related to nonalcoholic fatty liver disease (NAFLD), is an increasing trend among Asian people. The study aimed to assess the prevalence of NAFLD in T2DM with their risk factors in the Southern part of Pakistan. MATERIALS AND METHODS: A cross-sectional study was accomplished during 2008-2013 at The Aga Khan University Hospital, Karachi, Pakistan. Adult patients diagnosed with T2DM during last 6 months were enrolled in this study. NAFLD was identified using ultrasound of the liver. Clinical and biochemical relevant measurements were accomplished. RESULTS: Out of a total of 203 patients with T2DM, NAFLD was detected in 146 patients (71.9%). Multivariate analysis revealed that NAFLD was significantly associated with dyslipidemia (OR 2.38, 95% CI 1.06-5.34, p = 0.035), higher LDL (OR 1.02, 95%CI 1.01-1.03, p = 0.003), H bA1c (OR1.27, 95% CI 0.97-1.68, p = 0.045) and diastolic blood pressure (OR 1.05, 95% CI 1.01-1.10, p = 0.009). The highest odds of 10.8 for NAFLD (95% CI 4.9-24, p = 0.001) was found for the combination of hypertension, dyslipidemia, body mass index (BMI), waist circumference, lack of physical inactivity, triglycerides, lower HDL, LDL, HbA1c, and ALT (multiplicative analysis). CONCLUSION: High incidence of NAFLD with the association of different lifestyle-related factors has been analyzed. It unmasks the need for screening for NAFLD in newly diagnosed DM patients in Pakistan with the assessment of parameters of risk factors. HOW TO CITE THIS ARTICLE: Butt AS, Hamid S, et al. Nonalcoholic fatty Liver Diseases Among Recently Diagnosed Patients With Diabetes Mellitus and Risk Factors. Euroasian J Hepatogastroenterol 2019;9(1):9-13.